Letter from Dr. Joseph Klapp to James Curtis Booth, November 4, 1859 - Klapp, Joseph (1859)
Joseph Klapp writes concerning a trip to Richmond, Virginia by James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; Virginia--Richmond